A Case of More Is Less: The Role of Gender in U.S. Presidential Debates. (December 2015) - Turcotte, Jason; Paul, Newly
For candidates and voters alike, U.S. politics is a gendered space in which women are often underrepresented. Participation from women is assumed to equalize representation and voice in the political process; however, little research has explored gender influence on campaign agendas, particularly in non-news contexts. This study applies a quantitative content analysis to explore the influence of (1) candidate gender, (2) journalist gender, and (3) voter gender on the presidential debate agenda. In examining the issue focus of debate questions, we find that participation from women candidates and women journalists does little to improve agenda diversity and that the agendas set by women journalists fail to satisfy the issue priorities of women voters participating in these same debates.